Analisis Deskriptif Durasi dan Jumlah Konsumsi Rokok, Kadar Hemoglobin dan Tingkat Pengetahuan Bahaya Karbon Monoksida pada Petugas Kebersihan Jalan - Aulia Mutiara Hikmah; Zahara Fadilla; Randy Yusuf Kurniawan; Yuri Pradika; Gita Wideani (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
This study explores the relationship between smoking habits, hemoglobin levels, and awareness of carbon monoxide (CO) risks among street cleaning workers. Smoking is one of the most common sources of CO exposure, which can bind to hemoglobin and reduce oxygen transport in the body. A total of 67 street cleaning workers in West Jakarta were involved in this research, using a descriptive analytic approach. Data were collected through blood tests for hemoglobin levels, as well as interviews and questionnaires to assess smoking habits and knowledge of CO. The findings show that most respondents were light smokers (1–10 cigarettes per day), and 43% had been smoking for less than five years. While 66% of participants had normal hemoglobin levels, 33% had elevated levels, which may reflect the body’s response to reduced oxygen availability. Interestingly, 70% of respondents were aware of the health risks of CO, but knowledge tended to decline among long-term or heavy smokers. This indicates a gap between behavior and risk awareness. The study highlights the need for ongoing health education targeted at outdoor workers to increase understanding of CO exposure and prevent potential health impacts.